Innovative planting designs for oil palm-based agroforestry - Rival, A.; Ancrenaz, M.; Guizol, P.; Lackman, I.; Burhan, S.; Zemp, C.; Sulaiman, M. F.; Djama, M. (Springer Science and Business Media B.V., 2025)
Despite its commercial success, intensive oil palm monoculture is facing both social and environmental constraints. Adapting the traditional plantation model towards more resilient and climate-smart farming systems will require deep changes. Agroforestry offers great potential for biodiversity and carbon storage benefits while maintaining high palm oil yields. The TRAILS multidisciplinary research project has installed a 39-ha prototype experiment in Sabah, Malaysia. The project includes different planting designs (interplanted rows, mixed tree plantation and forest islands) aimed at providing information about: i) the ability of oil palm to grow in competition with forest trees, ii) the best combination of tree species and their compatibility with the oil palm constraints for co-cultivation, and iii) the growth and developmental characteristics of a selected number of native forest species of interest. More specifically, we plan to describe changes in biodiversity and ecosystem services together with oil palm performance.